Tip Speed Ratio Based MPPT Algorithm and Improved Field Oriented Control for Extracting Optimal Real power and Independent Reactive Power Control for Grid Connected Doubly Fed Induction Generator - D.V.N. Ananth; Gundavarapu Venkata Nagesh Kumar (Institute of Advanced Engineering and Science, 2016)
Doubly Fed Induction Generator (DFIG) needs to get adopted to change in wind speeds with sudden change in reactive power or grid terminal voltage as it is required for maintaining synchronism and stability as per modern grid rules. This paper proposes a controller for DFIG converters and optimal tip speed ratio based maximum power point tracking (MPPT) for turbine to maintain equilibrium in rotor speed, generator torque, and stator and rotor voltages and also to meet desired reference real power during the turbulences like sudden change in reactive power or voltage with concurrently changing wind speed. The performance of DFIG is compared when there is change in wind speed only, changes in reactive power and variation in grid voltage along with variation in wind speed.